2020
DOI: 10.1080/11356405.2020.1785138
|View full text |Cite
|
Sign up to set email alerts
|

What school social climate fa ctors affect mathematics performance in secondary school students? A multilevel análisis (¿Qué factores de Clima Social Escolar afectan el desempeño de Matemática en estudiantes secundarios? Un análisis multinivel)

Abstract: The international literature and public policy actions in education have positioned the school environment as a significant component of academic performance and the well-being of the entire educational community. The objective of this study is to identify the school social climate factors that affect secondary school students' academic performance in mathematics via a multilevel analysis. The model revealed the following factors: Disciplinary Measures, School Violence, Teacher-Student Violence and Encourageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…School violence is defined as any physical or psychological assault, or threat of assault, between participants in a school (Akiba et al, 2010). This behavior is present from the earliest years of schooling (Albaladejo-Blázquez et al, 2013) and serves as a predictor of the quality of social coexistence in schools (Córdoba et al, 2016) and academic performance (Bravo-Sanzana et al, 2020). Recent studies have shown that the relation between school attachment and violent behavior is mediated over time by violent attitudes (Varela et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…School violence is defined as any physical or psychological assault, or threat of assault, between participants in a school (Akiba et al, 2010). This behavior is present from the earliest years of schooling (Albaladejo-Blázquez et al, 2013) and serves as a predictor of the quality of social coexistence in schools (Córdoba et al, 2016) and academic performance (Bravo-Sanzana et al, 2020). Recent studies have shown that the relation between school attachment and violent behavior is mediated over time by violent attitudes (Varela et al, 2018).…”
Section: Introductionmentioning
confidence: 99%